PENGARUH PEREBUSAN PADA IMPREGNASI KAYU KARET - Harly Harly (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
Rubberwood is becoming more important in Indonesia and hence research for better treatment of this very susceptible wood species is badly needed. In general, the impregnation of the green wood results in a limited penetration.Boiling before preservative treatment by alternating pressure process greatly improved the treatment of rubberwood. A boiling period for one hour was sufficient to obtain required penetration of preservative.